O-linked N-acetylglucosamine is present on the extracellular domain of notch receptors. - Matsuura, A.; Ito, M.; Sakaidani, Y.; Kondo, T.; Murakami, K.; Furukawa, K.; Nadano, D.; Matsuda, T.; Okajima, T. (Journal of Biological Chemistry, 2008)
Rare types of glycosylation often occur in a domain-specific manner and are involved in specific biological processes. In particular, O-fucose glycans are reported to regulate the functions of EGF domain-containing proteins such as Notch receptors. In the course of mass spectrometric analysis of O-glycans displayed on Drosophila Notch receptors expressed in S2 cells, we found an unusual O-linked N-acetylhexosamine (HexNAc) modification which occurs at a site distinct from those of O-fucose and O-glucose glycosylations. Modification site mapping by mass spectrometry and amino acid substitution studies revealed that O-HexNAc modification occurs on a serine or threonine located between the fifth and sixth cysteines within the EGF domain. This modification occurs simultaneously along with other closely positioned O-glycosylations. This modification was determined to be O-beta-GlcNAc by galactosyltransferase labeling and beta-N-acetyl-hexosaminidase digestion experiments and by immunoblotting with a specific antibody. O-GlcNAc modification occurs at multiple sites on Notch epidermal growth factor repeats. O-GlcNAc modification was also found on the extracellular domain of Delta, a ligand for Notch receptors. Although the O-GlcNAc modification is known to regulate a wide range of cellular processes, the list of known modified proteins has previously been limited to intracellular proteins in animals. Thus, the finding of O-GlcNAc modification in extracellular environments predicts a distinct glycosylation process that might be associated with a novel regulatory mechanism for Notch receptor activity.